(untitled) (Bangladesh Journal of Agricultural Research, 2014)
The research work was carried out at the Seed Laboratory of Agronomy Department of Bangladesh Agricultural University, Mymensingh during the period from February to April in 2008 to find out the effect of hydropriming methods on maize seedling emergence. The hydropriming methods were- T1 (Non-priming), T2 (14 hours soaking + drying + storing), T3 (18 hours soaking + drying + storing), T4 (22 hours soaking + drying + storing), T5 (14 hours soaking + surface drying), T6 (18 hours soaking + surface drying), and T7 (22 hours soaking + surface drying). Effect of different hydropriming methods on seedling emergence performance of maize was evaluated at two moisture levels viz., 30% and 60% moisture of saturated sand in the experiment. Germination percentage, germination index and mean germination time were influenced significantly by hydropriming methods. The highest germination percentage, germination index, and lowest mean germination time were recorded with T6 (18 hours soaking + surface drying). DOI: http://dx.doi.org/10.3329/bjar.v39i1.20164 Bangladesh J. Agril. Res. 39(1): 143-150, March 2014